Internationalization of globalizing internationals into BRIC emerging markets. Case study: Wärtsilä’s internationalization into BRIC countries. - Lozano Segarra, Marta (My University, 2016)
In today’s globalized market place, it is of upmost important to learn how to approach a foreign market as well as what will have an effect on your methods of entry into this one. This project has sought to understand how the internationalization of globalizing internationals is seen affected when entering the BRIC emerging markets. There has been little research, prior to this study, looking into the foreign operation methods used by globalizing internationals when entering the BRIC countries as well as the influencing factors affecting these decisions. In order to gather data for the study, 12 semi-structured interviews were conducted on experienced workers from one case company. This allowed the data to have a bigger depth and provided a better understanding of the topic. The gathered data was organized into categories created thought the study’s theoretical framework and then analyzed in order to test the different hypothesis. In order to analyze the case company’s data, this study looks into their internationalization process, the effect that the change from an international to a global company has had on their operating methods, what motivates them to enter BRIC countries, what influences their entry mode selection into these countries, how they develop these operation methods as well as, why and when they re-evaluate and modify their entry method strategy. This study found that the main reason to enter the BRIC countries was the market potential as well as market access, and the customers’ location. Furthermore, some of the biggest influencing factors were the government and regulations, as well as the country’s economic development. Last but not least, the interviewees found that the most common reasons for FOM change were in order to react to a changing situation, divest from an undesired partnership or improve their governance. Method combination has only been tested to be used in order to manage unrelated business units. While the findings cannot be generalized, as they are based solely on one case company, this study sets the grounds for future research done on other markets and other companies.
Keywords: Internationalization; Globalization; Foreign business operation modes; Globalizing internationals; BRIC countries; emerging countries; influencing factors; mode package; mode switching.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|